Metformin Alleviates Autistic-Like Behaviors Elicited by High-Fat Diet Consumption and Modulates the Crosstalk Between Serotonin and Gut Microbiota in Mice - Wenlin Deng; Haoran Ke; Siqi Wang; Zitong Li; Sitao Li; Pinjing Lv; Fang Li; Ye Chen (Behavioural Neurology)
The biological mechanisms linking diet-related obesity and autistic behaviors remain unclear. Metformin has proven to be beneficial in the treatment of many syndromes, including autism spectrum disorder. Therefore, the aim of this study was to assess whether metformin treatment could ameliorate metabolic and behavioral alterations in C57BL/6 mice kept on a high-fat diet (HFD), and whether these changes were related to modifications in the gut microbiota and 5-HT levels. As expected, ten weeks of HFD ingestion increased body weight, adiposity, and glucose levels. HFD-fed mice showed a marked aggravation of repetitive behaviors (marble burying and self-grooming), and this was prevented by metformin administration. In addition, HFD-fed mice increased the total distance travelled in the open field test. This hyperactivity was counteracted by metformin cotreatment. In the elevated plus maze test, HFD-fed mice showed a reduced number of entries into the open arms. Interestingly, both HFD and metformin cotreatment increased social interactions in the three-chamber test. HFD increased the levels of intestinal tryptophan and 5-hydroxyindoleacetic acid. Metformin stimulated gut tryptophan and promoted the synthesis of 5-HT in the HFD group. Lactococcus, Trichococcus, Romboutsia, and Faecalibaculum were enriched in HFD-fed mice, whereas the HFD group cotreated with metformin was enriched in Intestinimonas and L. reuteri. Faecalibacterium was positively correlated with sociability and 5-HT pathway components in mice that received metformin. In summary, HFD consumption elicited a complex phenotype comprising higher levels of anxiety-like and repetitive behaviors but also increased sociability. Metformin could potentially improve HFD-induced disorders in the autistic spectrum through a mechanism involving positive modulation of 5-HT levels in the gut and its microbiota composition.